Analisa Penerapan Entrepreneurial Marketing Syaria dan Dampaknya Terhadap Kinerja Usaha (Studi Pada Pelaku Usaha UMKM Kerajinan Keramik di Banjarnegara) - Aulia, Nafisa Farkhiy; Dirgantara, I Made Bayu (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the application of entrepreneurial marketing and its impact on business performance (Study on Micro, Small and Medium Enterprises Entrepreneurs in Banjarnegara). The qualitative method uses the question model "how" and "why" related to a phenomenon, while the quantitative method is more in the form of questions in the opposite form. The qualitative method is also a method that focuses on in-depth observation. Based on the results of interviews and documentation studies, it can be concluded that the majority of business actors have implemented proactiveness in running their business, although not all of them have implemented it optimally. In general, the informants have understood the concept of opportunity focus and have applied it quite well to their respective businesses. All sources are aware of how their respective business positions are compared to their competitors. And each business actor has a strategy for running his business, even when one of the informants experienced a setback in his business, now he is trying to get up and restart his business slowly by implementing an opportunity focus. Based on the results of the interviews, it can be concluded that all the informants have understand what entrepreneurial marketing is and have implemented customer intensity or the ability to maintain good relations with consumers properly. Based on the results of the interviews, most of the Banjarnegara ceramics business actors are aware of the importance of having an open mind towards new ideas in finding new customers, determining prices, and also packaging. However, almost all interviewees have not implemented innovation in running their business to the fullest. Judging from the results of the interviews, the application of risk taking to Banjarnegara ceramic entrepreneurs is quite good. Based on the results of the interviews, it appears that the interviewees are aware of and understand the potential of their human resources. Based on the interview results, all interviewees agreed that implementing value creation in doing business is very important.